2011
DOI: 10.1002/hed.21366
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy for accessory nerve shoulder dysfunction following neck dissection surgery: A literature review

Abstract: There is a need for research to investigate the effects of early, appropriate physiotherapy on the development of ANSD following neck dissection surgery. Such a study has the potential to improve the functional outcome and quality of life in this patient group, and ultimately to promote best practice guidelines for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 124 publications
(113 reference statements)
1
43
0
3
Order By: Relevance
“…[13][14][15] A metaanalysis examining the effect of RET on QOL for all cancers reported a small clinical benefit from resistance exercise immediately post-intervention; 14 because few of the included studies reported follow-up data, however, the authors were not able to draw conclusions on longterm effects. 14 Our follow-up results show that benefits are largely sustained over the follow-up period and that further improvement may also occur in the subgroup of participants who continue regular RET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] A metaanalysis examining the effect of RET on QOL for all cancers reported a small clinical benefit from resistance exercise immediately post-intervention; 14 because few of the included studies reported follow-up data, however, the authors were not able to draw conclusions on longterm effects. 14 Our follow-up results show that benefits are largely sustained over the follow-up period and that further improvement may also occur in the subgroup of participants who continue regular RET.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is one of the first to provide follow-up data on a resistance exercise intervention for shoulder pain and dysfunction after neck dissection in HNC survivors. [13][14][15] Because the study design allowed crossover for participants originally assigned to the TP group, we did not anticipate continued group differences at 12-month follow-up based on randomization. We were interested to determine, however, whether any benefits from the 12-week PRET intervention persisted over the longer term.…”
Section: Ré Sumémentioning
confidence: 99%
“…Literature data also support our findings. High recovery potential has been shown after accessory nerve injuries in the recent literature (30,31). Akgun et al (30), showed that conservative management is effective even in late diagnosed spinal accessory nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, physical therapists must be aware of the decline in nutritional status after surgery or chemoradiation in these patients [57]. Paralysis of accessory nerve that causes trapezius muscle dysfunction is often seen following neck dissection [58]. This dysfunction leads to shoulder syndrome with adhesive capsulitis.…”
Section: Common Dysfunctions In Head and Neck Tumormentioning
confidence: 99%